Tinjauan Yuridis Tentang Kepastian Hukum Kewenangan Perusahaan Dalam Penggeledahan Ponsel Pribadi Karyawan - Joshua Evandeo Irawan (KRTHA BHAYANGKARA, 2023)
The use of sophisticated smartphones in the world of work often causes problems such as those that occur in PT. X, where a worker, Mrs. A, in early 2022, was forced to give her smartphone to be searched on orders from the Director of PT. X, named Mrs. B. The search warrant came as the alleged hate speech expressed by Mrs. A about Mrs. B to fellow workers via Whatsapp text message. The writing of this article aims to answer the big question of whether companies are authorized to check their employees' mobile phones in terms of the positive law in Indonesia, namely the ITE Law. The writing of this article uses the dogmatic normative juridical method by approaching it through statutes approach and conceptual approach. The final result of this article is that Mrs. A's smartphone is the personal property of Mrs. A where all data in the cellphone is private property protected by Article 26 paragraph (1) of the ITE Law jo Article 30 paragraph (1) of the ITE Law while Mrs. B as the Director of PT. X can conduct a search because Mrs. B is not classified as an investigator as explained in Article 43 of the ITE Law